UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) PADA SISWA KELAS IV SDN 1 SUMBEREJO KECAMATAN KEMILING BANDAR LAMPUNG TAHUN PELAJARAN. 2014 /2015 - Sarifah, Sarifah (LPPM STKIP PGRI Bandar Lampung, 2015)
In general, mathematics is a subject that is considered difficult and disliked by students. Students do not like math because it was difficult to follow. Therefore the mathematics learning outcomes are not as expected. The aim of this study is Improving math learning activities and results of fourth grade students at SDN 1 Sumberejo District of Kemiling.This study uses a Class Action Research (PTK). Planned implementation two cycles each cycle consists of four phases: Planning, Acting, Observing, Reflecting. Action Research (PTK) was conducted at SDN 1 Sumberejo Class IV in the second half in the school year 2014/2015 the number of students 20 consists of 6 female students and 14 male studentsApplication Cooperative Learning of TAI model’s can improve student Learning Activities and Results of Operations discussion on the subject of class IV SDN Calculate Numbers 1 Sumberejo. This indicated an increase in each cycle with the details as follows: for the percentage of students learning activity first cycle (40%) and the second cycle (100%). Improved student learning outcomes indicated by the increasing percentage of mastery learning is at the first cycle (60%), Cycle II (85%)